Relaxation and frequency response analysis studies on power equipment - Yu, Xingzhou. (2008)
The main objective of this research project is to study the relaxation processes in various power apparatus of two power-generating plants with Recovery Voltage Measurement (RVM) and Polarization Current Measurement (PCM) techniques and to develop an automated technqiue to identify winding faults and severity of a transformer using Frequency Response Analysis (FRA) technqiue.